Analisis Efektivitas Pelatihan Truck Safety Awareness (TSA) kepada Pengemudi Truk terhadap Perilaku Aman Berkendara di Pelabuhan Tanjung Priok - Abdur Rafi Addarajad; Marihot Simanjuntak; Rosmayana Rosmayana; Inayatur Robbany (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The maritime industry currently faces the challenges of rapid digital transformation, yet the human factor remains a key pillar in ensuring safe port operations. This study aims to analyze the effectiveness of Truck Safety Awareness (TSA) training on the safe driving behavior of truck drivers at Tanjung Priok Port. The main issue raised is the high risk of accidents in the terminal area due to external driver behavior, the impact of which has not been scientifically validated. Using a descriptive qualitative approach with purposive sampling, primary data were collected through in-depth interviews with truck drivers, focus group discussions (FGDs) with port management, and direct field observations at critical operational points. Thematic analysis results indicate that the TSA program has proven highly effective and efficient in shifting driver safety paradigms. This success was significantly driven by a hyper-contextual curriculum and visual delivery methods that utilized real-life accident case studies at the research site. These findings demonstrate that internalization of awareness can bridge the gap between theoretical knowledge and real-world actions, even under high operational pressure. This study provides a significant contribution to port management in validating safety training investments as a sustainable risk mitigation strategy. In practice, the TSA serves as a best practice model that balances port logistics efficiency and optimal occupational safety standards to support maritime supply chain resilience.